2015
DOI: 10.1002/mus.24703
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity 3-dimensional reachable workspace assessment in amyotrophic lateral sclerosis by Kinect sensor

Abstract: Introduction Reachable workspace is a measure that provides clinically meaningful information regarding arm function. In this study, a Kinect sensor was used to determine the spectrum of 3D reachable workspace encountered in a cross-sectional cohort of individuals with ALS. Method Bilateral 3D reachable workspace was recorded from 10 subjects with ALS and 23 healthy controls. The data were normalized by each individual's arm length to obtain a reachable workspace relative surface area (RSA). Concurrent valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…No correlation was observed between the Z-score and the ALSFRS-R score. Although the ALSFRS-R score does correlate with overall disease progression in ALS [13] it has been shown as inadequate to accurately describe functional loss in performing arm movements [6]. The lack of correlation between the Z-score and the ALSFRS-R score may be due to a similar limitation of the ALSFRS-R to quantify functional loss in head movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No correlation was observed between the Z-score and the ALSFRS-R score. Although the ALSFRS-R score does correlate with overall disease progression in ALS [13] it has been shown as inadequate to accurately describe functional loss in performing arm movements [6]. The lack of correlation between the Z-score and the ALSFRS-R score may be due to a similar limitation of the ALSFRS-R to quantify functional loss in head movements.…”
Section: Discussionmentioning
confidence: 99%
“…These devices are portable, easy to use and relatively inexpensive. Nevertheless, they evaluate only isolated strength over specific muscle groups and do not provide an assessment of the overall function of a joint [6]. Thus, an assessment based only on muscle strength evaluation conveys limited information with regard the actual level of progression of the disease and there is a need for the development of tools that enable a more function based objective quantitative assessment of execution of movement.…”
Section: Introductionmentioning
confidence: 99%
“…The Kinect depth camera can completely overcome the above shortcomings. This camera can reliably measure the 3D reachable workspace [8], which is inexpensive and can be easily integrated into practical applications [9] to identify target crops. At present, Microsoft’s Kinect depth camera includes Kinect v1 and Kinect v2.…”
Section: Kinect V2 and Camera Calibrationmentioning
confidence: 99%
“…Chang et al [20] developed a Kinect-based rehabilitation system for physical rehabilitation in public school settings. Han et al demonstrated the clinical significance and effectiveness of the Kinect-based reachable workspace in Duchenne muscular dystrophy (DMD) and amyotrophic lateral sclerosis (ALS) [21][22][23].…”
Section: Introductionmentioning
confidence: 99%